Does Geographical Indication Certification Increase the Technical Complexity of Export Agricultural Products? - Xu, Zhiyuan; Feng, Yang; Wei, Hua (Frontiers in Environmental Science, 2022)
As a special intellectual property right, geographical indications have obvious regional quality signals and reputation. Whether geographical indication certification can promote the technical complexity of export agricultural products in the process of high-quality agricultural transformation in developing countries is a new issue that has to be studied urgently. Therefore, based on the provincial panel data from 2005 to 2019, this research examines the impact of geographical indication certification on the technical complexity of China's export agricultural products. The empirical results reveal that geographic indication certification can significantly improve the technical complexity of export agricultural products. Moreover, the positive spillover effect of geographical indications on the export of agricultural products is strengthened as the level of the technical complexity of products increases. However, the regression coefficient at the 85% quantile decreases, reflecting that the current international recognition of geographical indication certification in China needs improvement. The heterogeneity study finds that the above results are not significantly supported by evidence in the central region. Thus, the quality guidance role of geographical indication products in the central region has not been brought into full play, thereby restraining the price addition ability of export agricultural products. Therefore, the government should increase policy support to enhance the quality guidance role of geographical indication products.